2007
DOI: 10.2478/s11658-007-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultracentrifugation studies of the location of the site involved in the interaction of pig heart lactate dehydrogenase with acidic phospholipids at low pH. A comparison with the muscle form of the enzyme

Abstract: Lactate dehydrogenase (LDH) from the pig heart interacts with liposomes made of acidic phospholipids most effectively at low pH, close to the isoelectric point of the protein (pH = 5.5). This binding is not observed at neutral pH or high ionic strength. LDH-liposome complex formation requires an absence of nicotinamide adenine dinucleotides and adenine nucleotides in the interaction environment. Their presence limits the interaction of LDH with liposomes in a concentration-dependent manner. This phenomenon is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Native enzymes GOx, AP, Lip and LDH move towards the positive electrode due to the net negative charge on these enzymes. 36 The staining of HRP in the gel is very poor and its electrophoretic properties could not be established. The MECs will have high molecular weight and may remain in the loading well without any movement through the gel.…”
Section: Resultsmentioning
confidence: 99%
“…Native enzymes GOx, AP, Lip and LDH move towards the positive electrode due to the net negative charge on these enzymes. 36 The staining of HRP in the gel is very poor and its electrophoretic properties could not be established. The MECs will have high molecular weight and may remain in the loading well without any movement through the gel.…”
Section: Resultsmentioning
confidence: 99%
“…This was also spectrometry. Although several proteins were claimed by Terlecki et al (47) for lactate identified, their individual binding characteristics dehydrogenase-phosphatidylserine interaction. and affinity for the phosholipid have not been The mammalian M2 type pyruvate kinase determined in each case.…”
Section: Pyruvate Kinase Forms a Complex With Clathrinmentioning
confidence: 98%